Intrinsic and extrinsic motives of undergraduate students for pursuing a master’s degree: Applying the Eccles et al. expectancy-value model - Susanne Bergann; Irmela Blüthmann; Martin Neugebauer; Rainer Watermann (PLoS ONE, 2025)
This study investigates the factors driving students to pursue a master’s degree, taking into account the mediating role of ability beliefs in this decision-making process. Previous research has primarily focused on a narrow range of explanatory factors, such as the utility value of a master’s degree and associated monetary costs. Yet, the role of intrinsic value, expectations of success, and psychological costs of failure, which are crucial in the decision to pursue further studies, have been insufficiently explored. Drawing on the expectancy-value model by Eccles et al., this study develops a comprehensive model to examine the factors influencing bachelor’s students’ intentions to pursue a master’s degree. Using structural equation modelling (SEM) to analyse cross-sectional data from N =  3,044 undergraduate students at a major German university, our findings provide robust support for the theoretical framework. Specifically, students’ expectations of successfully completing a master’s degree emerged as the strongest predictor of their intentions to transition (β = .42, p <  0.001). Intrinsic value, indicated by interest in scientific work, proved to be as important as the utility value (β = .36, p <  0.001). Moreover, psychological costs significantly influenced student’s decisions (β =  -.21, p <  0.01). Notably, apart from academic performance, beliefs about general and scientific abilities contributed to both the expectancy and value components of the model. These results provide valuable insights for higher education institutions regarding programme development and counseling services aimed at supporting students during this critical decision-making process. Additionally, this study enriches the theoretical understanding of the complex dynamics involved in student’s academic transitions.